Promotional strategies effects on listeners and to AM and FM radio station - Agravante, Vanessa; Aguirre, Mary Vanessa Hope.; Espinosa, Iris.; Gallo, Sheila May. (2002.)
Executive summary - Radio Communication is the most convenient form of information dissemination. It can reach even the far-flung areas of the Philippines. Most radio stations are operating on air nationwide, thus competition is very stiff. In order to withstand competition, certain promotional strategies are being employed by the station. In this connection, the study was conducted to determine the effects of promotional strategies on listeners and on AM and FM radio stations, particularly in Iloilo City. The study covered four (4) AM and eight (8) FM radio stations in Iloilo City. With a tight competition existing, these stations strive to gain additional audience to increase rating and attract more advertisers thus, increasing its revenue. With this tight race to be on top, those radio stations have conducted promotional strategies. The promotional strategies employed have been named th second reason why people listen to a particular radio station. The prizes at stake, such as cash, gift cheques and grocery items, were the factors that contribute to the enthusiasm of the listeners to join. This action can be attributed to the present economic state of the country, wherein unemployment is very rampant. The target market of these stations are class A, B, C, D, and E. However, classes C and D have been the stations' most preferred target market. The said classes are those who are unemployed and financially unstable.For the listeners, the belief that they indeed have a great part in increasing the radio station's rating and revenue. have been attested in the responses made in the questionnaires. This only proved that promotional strategies have been effectively and efficiently serving its purpose
Research Paper (BA 200 - Business Research) -- [Iloilo City] : University of the Philippines in the Visayas - College of Management, March 2002